The effect of quercetin on cyclosporine-A-induced cardiotoxicity in adult male albino rats: a histological and immunohistochemical study. Issue 3 (September 2015) - El-Mahalaway, Abeer M.; Selim, Amal A.; Razzak Mahboub, Faiza Abdul
Abstract : Background: Cyclosporine-A (Cs-A) is the most widely used immunosuppressive agent in organ transplantation and autoimmune disease treatment. Nevertheless, its therapeutic use is associated with serious effects, including cardiotoxicity. Quercetin is one of the naturally occurring flavonoids present in a lot of the human diets. Objective: The aim of this study was to evaluate the effect of quercetin on cyclosporine-induced cardiotoxicity in adult male albino rats. Materials and methods: Forty adult male rats were included and divided into four groups (10 rats each): group I was the control group; group II (the quercetin group) rats received daily intraperitoneal injection of quercetin (15 mg/kg body weight/day) for 4 weeks; group III (the cyclosporine group) rats received daily subcutaneous injection of Cs-A (20 mg/kg body weight/day) for 4 weeks; and group IV (the cyclosporine and quercetin group) rats received Cs-A and quercetin for 4 weeks. Heart specimens were taken and processed for light microscopy study (H&E and Masson's trichrome staining and immunohistochemical staining for caspase-3) and electron microscopy study. Results: Group III showed prominent myocardial fiber degeneration with areas of myofibril loss and interstitial hemorrhage. This was supported by the positive reaction for apoptotic marker caspase-3. An increase in the collagen fibers in the endomysium was obvious. Electron microscopic results showed irregular nucleus with disruption of the sarcolemma and intercalated discs. The cytoplasm showed an area of myofibril loss and mitochondrial swelling. Group IV showed improvement in most light and electron microscope changes described before. Conclusion: Quercetin can be a natural cardioprotective agent and can be used to improve cyclosporine-induced cardiotoxicity, as it has antioxidant and anti-inflammatory enzyme activities. We advise taking a diet rich in quercetin or dietary supplementation.